Taking it outside: A study of legal contexts and external whistleblowing in China and India - Sebastian Oelrich; Kimberly Erlebach (Asian Journal of Business Ethics, 2021)
Whistleblowing is regularly identified as corporate control mechanism to prevent and uncover fraud. We review and compare the legal situation for whistleblowers in the People's Republic of China and India. In a survey of 942 employees from private companies in both countries, we take a look at the status quo of whistleblowing system implementation, explore preference of channels to disclose fraud or corruption, and analyze under which conditions and what kind of employees prefer external over internal whistleblowing. We find that provisions for mandatory whistleblowing systems can be found in the law of both countries. In China in particular, protection is scattered across many different laws in the private sector. Indian companies seem to have systems in place more often, although this difference becomes smaller the larger the company. The general preference of internal over external channels is similar across countries. Our regression models suggest that external channels are preferred over internal ones when fear of retaliatory measures is higher, the company is smaller, and the whistleblower is female. In line with prior literature, the effect of fear of retaliation is moderated by gender: women are less influenced by retaliation. All in all, implementation of whistleblowing systems seems ubiquitous in both countries; legal protection and comprehensive measures to decrease retaliation are lacking. Additional implications of findings are discussed.
Keywords: 330; External whistleblowing; Corporate governance; China; India; Whistleblowing systems; Fraud; Whistleblowing legislation